Discussion: The Determinants of Bank Interest Margins: Theory and Empirical Evidence - Lerner, Eugene M. (Journal of Financial and Quantitative Analysis, 1981)
In this paper Ho and Saunders apply a model that has been used to analyze dealer spreads to banking.A potential contribution to a field can arise whenever a well-developed framework of analysis in one problem area is applied to another field. The risk of a mechanical application, however, is that the institutional structure of the two problem areas is so different that no real insights are gained. What are the facts here?